Comparing alternate learning pathways within a problem-based learning speech-language pathology curriculum. - Erickson, Shane; Serry, Tanya Anne (International Journal of Speech-Language Pathology, 2016)
Purpose: This qualitative study investigated the learning process for speech-language pathology (SLP) students engaging in a problem-based learning (PBL) curriculum and compared the perspectives of students from two pathways. Method: Sixteen final-year SLP students participated in one of four focus groups. Half the participants entered the course directly via an undergraduate pathway and the other half entered via a graduate entry pathway. Each focus group comprised two students from each pathway. Data were generated via a semi-structured interview and analysed thematically. Result: Regardless of participants' pathway, many similar themes about factors that influenced their expectations prior to PBL commencing as well as their actual PBL experiences were raised. Participants believed that PBL was a productive way to learn and to develop clinical competencies. Many were critical of variations in PBL facilitation styles and were sensitive to changes in facilitators. The majority of participants viewed experiential opportunities to engage in PBL prior to commencement of semester as advantageous. Conclusion: Combining students with different backgrounds has many advantages to the PBL learning process. Regardless of prior experiences, all students must be sufficiently prepared. Furthermore, the facilitator has a crucial role with the potential to optimise or detract from the learning experience.